Spontaneous tandem sequence duplications reverse the thermal stability of carboxyl-terminal modified 3-isopropylmalate dehydrogenase. - Akanuma, S (1996)
A mutant strain of Thermus thermophilus which contains deletions in the 3'-terminal region of its leuB gene showed a temperature-sensitive growth phenotype in the absence of leucine. Three phenotypically thermostable mutants were isolated from the temperature-sensitive strain by spontaneous evolution. Each pseudorevertant carried a tandem sequence duplication in the 3' region of its leuB gene. The mutated 3-isopropylmalate dehydrogenases encoded by the leuB genes from the pseudorevertants were more thermostable than the enzyme from the temperature-sensitive strain. Structural analyses suggested that the decreased thermostability of the enzyme from the temperature-sensitive strain was caused by reducing hydrophobic and electrostatic interactions in the carboxyl-terminal region and that the recovered stability of the enzymes from the pseudorevertants was due to the restoration of the hydrophobic interaction. Our results indicate that tandem sequence duplications are the general genetic way to alter protein characteristics in evolution.